Konferencija The Future of Information Sciences - INFuture2007: Digital Information and Heritage, Zagreb, 7.-9. studenoga 2007. - Stančić, Hrvoje (Array, 2008)
U radu je prikazana međunarodna znanstvena konferencija The Future of Information Sciences - INFuture2007: Digital Information and Heritage.